Amplified emission and modified spectral features in an opal hetero-structure mediated by passive defect mode localization. (12th December 2017) - Rout, Dipak; Kumar, Govind; Vijaya, R
Abstract: A photonic crystal hetero-structure consisting of a passive planar defect of SiO2 thin film sandwiched between two identical opals grown by inward growing self-assembly method using Rhodamine-B dye-doped polystyrene microspheres is studied for the characteristics of dye emission. The optical properties and the defect mode characteristics of the hetero-structure are studied from the reflection and transmission measurements. Laser-induced fluorescence from the hetero-structure showed amplified and spectrally narrowed emission compared to the photonic crystal emphasizing the role of the defect mode and distributed feedback. The enhanced emission is also complemented by the reduction in fluorescence decay time in the case of the hetero-structure in comparison to the 3D photonic crystals.